Reading for Understanding Toward an R&D Program in Reading Comprehension - Snow, Catherine (RAND Corporation, 2002)
In fall 1999, the Department of Education's Office of Educational Researchand Improvement (OERI) asked RAND to examine how OERI might improve thequality and relevance of the education research it funds. The RAND ReadingStudy Group (RRSG) was charged with developing a research framework toaddress the most pressing issues in literacy. RRSG focused on readingcomprehension wherein the highest priorities for research are: (1)Instruction